The Influence of Metal-Doped Graphitic Carbon Nitride on Photocatalytic Conversion of Acetic Acid to Carbon Dioxide - Sakuna, Pichnaree; Ketwong, Pradudnet; Ohtani, Bunsho; Trakulmututa, Jirawat; Kobkeatthawin, Thawanrat; Luengnaruemitchai, Apanee; Smith, Siwaporn Meejoo (Frontiers in Chemistry, 2022)
Metal doped graphitic carbon nitride (MCN) materials have shown a great promise as an effective photocatalytic activity in photooxidation of acetic acid under UV-visible irradiation, being superior than a pristine carbon nitride (g-C3N4, CN). In this study, effects of metal dopants in metal doped CN samples (Fe-, Cu-, Zn-, FeCu-, FeZn- and CuZn-doped CN) on their physicochemical properties and photo-oxidation of acetic acid were investigated and discussed for their correlation especially on their surface and bulk structures. The materials in order of highest to lowest photocatalytic activity are FeZn_CN, FeCu_CN, Fe_CN, and Cu_CN (giving the rate of CO2 evolution higher than CN), followed by Zn_CN, CuZn_CN, and CN. Extended ranged light absorption was the resulted of Fe doping while their crystalline phase, morphology, and specific surface area were not significantly modified by the incorporation of any metal studied. Although the light absorption was extended into the visible region, the photocatalytic efficiency using the modified CN could not be explained by this phenomenon. To further understand this issue, the materials were analyzed by two complementary techniques, reversed double-beam photoacoustic (RDB-PA) and electron spin resonance (ESR) spectroscopy. The FeZn_CN, with the highest electron trap density between 2.95 and 3.00 eV showed the highest CO2 evolution obtained from acetic acid photodecomposition. In addition, all Fe incorporated CN materials and Cu-CN can be categorized as a high activity catalyst according to the high rates of CO2 evolution obtained. Both RDB-PA and ESR techniques can be used to classify the highly effective CN based catalysts giving the CO2 evolution rate higher than 0.15 mol/min-1, >1.5 time higher than that of the pristine CN. Results from this research suggested a correlation between the rates of CO2 evolution via photocatalytic oxidation of acetic acid and threshold number of free unpaired electron in CN based materials and the high electron trap density between 2.95 and 3.00 eV.